In vitro permeation of platinum through African and Caucasian skin - Franken, A.; Eloff, F.C.; du Plessis, J.; Badenhorst, C.J.; Du Plessis, J.L. (Toxicology letters, 2015)
•Platinum permeated through intact African skin.•Significantly higher platinum permeation through African skin.•Retention of platinum in the skin is significantly higher in African skin.•Retention of platinum in the skin could contribute to dermal symptoms.•Increased permeation through African skin is contradictory to limited literature. The majority of the South African workforce are Africans, therefore potential racial differences should be considered in risk and exposure assessments in the workplace. Literature suggests African skin to be a superior barrier against permeation and irritants. Previous in vitro studies on metals only included skin from Caucasian donors, whereas this study compared the permeation of platinum through African and Caucasian skin. A donor solution of 0.3mg/ml of potassium tetrachloroplatinate (K2PtCl4) dissolved in synthetic sweat was applied to the vertical Franz diffusion cells with full thickness abdominal skin. Skin from three female African and three female Caucasian donors were included (n=21). The receptor solution was removed at various intervals during the 24h experiment, and analysed with high resolution inductively coupled plasma-mass spectrometry (ICP-MS). Skin was digested and analysed by inductively coupled plasma-optical emission spectrometry (ICP-OES). Significantly higher permeation of platinum through intact African skin (p=0.044), as well as a significantly higher mass of platinum retention in African skin in comparison with Caucasian skin (p=0.002) occurred. Significant inter-donor variation was found in both racial groups (p<0.02). Results indicate that African workers have increased risk of dermal permeation and therefore possible sensitisation caused by dermal exposure to platinum salts. These results are contradictory to limited literature suggesting a superior barrier in African skin and further investigation is necessary to explain the higher permeation through African skin.